Southern right whales (Eubalaena australis) return to a former wintering calving ground: Fowlers Bay, South Australia - Charlton, Claire; Ward, Rhianne; McCauley, Robert; Brownell, R.L.; Guggenheimer, Sasha; Salgado Kent, Chandra; Bannister, J.L. (WILEY, 2019)
© 2019 Society for Marine Mammalogy